2019
DOI: 10.17221/40/2018-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of GHRL, GHSR, LEP, LEPR, SST and CCK genes in the gastrointestinal tissues of Tibetan and Yorkshire pigs

Abstract: The aim was to characterize the expression patterns of several genes in the gastrointestinal tracts of Tibetan pigs (TP) and Yorkshire pigs (YP) and to explore their correlation with digestion and growth difference of the two breeds. The body weights and growth of YP and TP were studied at 6, 12 and 24 weeks of age, and their plasma levels of ghrelin (GHRL), leptin (LEP), somatostatin (SST) and cholecystokinin (CCK) were determined by enzyme linked immunosorbent assay (ELISA). Blood and gastrointestinal sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…This may seem a coincidence, as the GHSR encodes a receptor for ghrelin, which in turn acts in opposition to leptin encoded by the LEP. However, a study previously cited by us showed a similar pattern of GHSR and LEP gene expression in pigs [33]. As similar results were obtained in studies with two different species, this aspect needs to be carefully examined in future studies.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This may seem a coincidence, as the GHSR encodes a receptor for ghrelin, which in turn acts in opposition to leptin encoded by the LEP. However, a study previously cited by us showed a similar pattern of GHSR and LEP gene expression in pigs [33]. As similar results were obtained in studies with two different species, this aspect needs to be carefully examined in future studies.…”
Section: Discussionsupporting
confidence: 72%
“…On the other hand, studies conducted on young Tibetan and Yorkshire pigs have revealed GHSR mRNA expression in all examined organs of the GIT, namely the stomach, small intestine, cecum, and colon. The highest expression levels have been found in the duodenum and jejunum [ 33 ]. The expression of GHSR has also been studied in rat and guinea pig GIT organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paved the way for the melanocortin pathway (appetite regulation pathway), which consists of the satiety signaling pathway (regulated mainly by LEP, LEPR and MC4R) and the appetite signaling pathway (regulated among others by GHRL) (Męczekalski et al 2008). Ghrelin is a 28-amino acid peptide, identified as an endogenous ligand for the growth hormone secretagogue receptor (GHS-R), and it was isolated from the stomach of rats, humans and pigs (Kojima et al, 1999;Takaya et al, 2000;Salfen et al, 2004;Sun et al, 2019). Ghrelin conducts its biological activity through interaction with its specific cell surface receptor (GHS-R), that belong to G protein-coupled receptors, and for which two subtypes have been described: GHS-R type 1a (functional) and GHS-R type1b (nonfunctional) (van der Lely et al, 2004).…”
mentioning
confidence: 99%